A study to evaluate the accuracy of MRI in comparison to knee arthroscopy in diagnosing cruciate ligament tear and meniscal tears in organized sports and physical exercise related knee injuries in armed forces personnel - Bucha, Atul; Dashottar, Sunita; Sharma, Surabhi; Pany, Preeth; Suthar, Rushabh Bhikhanhai (International Journal of Advances in Medicine, 2018)
Background: Knee injuries related to organised sports and physical training related activities are a major component of injuries sustained by armed forces personnel. Knee instability caused by meniscal and ligamentous injuries cause varying degree of disabilities to the trained soldier and have a serious implication on the battle preparedness of the armed forces. MRI of the knee being a non-invasive modality is being increasingly used in pre and post op evaluation of patients in such cases. Methods: A prospective observational study comprising of 161 patients of knee injuries sustained due to sports and physical training related activities was carried out. MRI and arthroscopic examination of the knee was done, and various statistical tests were performed to evaluate the accuracy of MRI in comparison to arthroscopy. Results: ACL tears were seen in 122 patients (75.5%), PCL tears were seen in 67 patients (41.6%), while medial and lateral meniscus tears were noted in 93 (57.7%) and 50 (31%) patients respectively. The sensitivity and specificity of MRI in detecting ACL tear, PCL tear and medial meniscus injury ranged from 84% - 90.5% and for lateral meniscus it was 72.92% to 86.73 %. The accuracy of MRI in detecting the tear of ACL, PCL and menisci ranged from 82.61% to 89.97%. Conclusions: The accuracy of MRI in detection of meniscal and ACL tears is very high. Pre-operative MRI in conjunction with adequate history and physical examination can help the clinician to make an accurate diagnosis and can help reduce unnecessary arthrosopic surgeries.